Pelatihan Kemampuan Menulis Esai Argumentatif bagi Siswa SMA Negeri 7 Ambon melalui Pendekatan Kontekstual - Lewier, Mariana; Hiariej, Chrissanty (Universitas Pattimura, 2024)
The ability to write argumentative essays is one of the important language skills in developing critical thinking and written communication skills. However, this skill is still a challenge for most high school students, who are often unable to organize arguments logically and systematically. The low level of this skill is due to the learning approach that is not fully contextualized and the lack of directed practice. In response to these conditions, the Community Service team from the Indonesian Language Education Study Program conducted training activities on writing argumentative essays using a contextual approach at SMA Negeri 7 Ambon. This activity began with the provision of intensive training, which included understanding the structure of the essay, techniques for composing arguments, and the use of effective language. The training was followed by direct writing practice assisted by lecturers to 30 grade XI students. The results of the activity showed an increase in the participants' ability to compose essays that were more structured, contained relevant arguments, and were more confident in expressing their opinions through writing. Most students were also able to relate essay topics to their personal experiences and the surrounding environment. This activity proves that the contextual approach is effective in improving the quality of students' argumentative writing and encouraging the formation of critical thinking attitudes.